Thoracic intramedullary lipoma in a 3-year-old child: Spontaneous decrease in the size following incomplete resection - Yilmaz, Cem; Aydemir, Fatih (Asian Journal of Neurosurgery, 2018)
Nondysraphic intramedullary spinal cord lipomas are even rarer. We present a thoracic intramedullary lipoma which spontaneously decreased in size following surgical debulking. A 3-year-old girl was admitted to our department with complaints of back pain since 1 year and progressive difficulty in walking since 6 months. Her magnetic resonance imaging (MRI) revealed T8-9 intramedullary mass showing increased signal intensity in both T1- and T2-weighted images. The patient was operated with a T8-9 laminoplasty and debulking, and internal decompression of the tumor was made. Histologically, the tumor was uniformly composed of mature adipose tissue revealing a lipoma. First-month control MRI revealed the rest mass almost the half volume of the preoperative mass. The 2nd year MRI revealed the size of the lipoma was spontaneously decreased to almost half of postoperative size and 3rd year was the same as the 2nd year with a mild kyphosis. Decompression and debulking with or without duraplasty is the most appropriate treatment for symptomatic patients. Dietary measures with control of fat intake and long-term follow-up are also suggested.
Keywords: Intramedullary; lipoma; spontaneous decrease